Biodiversity Strategy with Focus on Urban Solutions - Krynina, Vlada; Fischer, Jakub, 1978-; Přech, Jiří; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
This thesis aims to explore the current state and time evolution of European biodiversity, with a particular focus on the Czech Republic, using data analysis methods. The Earth's biodiversity plays a crucial role in human life, providing food, medicines, and essential chemical elements, as well as serving as a source of oxygen. However, preserving this biodiversity has become a major challenge, and this thesis seeks to understand how the problem of biodiversity degradation can be addressed through urban development and how to measure a diversity of species in a specific area. By emphasizing the significance of conserving biodiversity and supporting sustainable urban development, this research adds to the increasing number of research initiatives that aim to tackle the urgent problem of biodiversity decline. The research questions investigated throughout this thesis are as follows: -How to measure the diversity of species in a given area and country? -Which country shows better results of diversity of species and why?
Vedoucí práce: Jakub Fischer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: official statistics [obor dipl. práce]; diplomové práce; master's theses